2011
DOI: 10.1002/jcla.20438
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the automated fluorescence microscopic viability test with the conventional and flow cytometry methods

Abstract: The cell viability test is an essential tool in any laboratory, performing cell-based studies and clinical laboratory tests. The trypan blue exclusion method is the most popular assay for its simple concept among various diagnostic tools. However, several disadvantages include time-consuming and labor-intensive steps with low precision. In this study, we evaluated a new technique for the automatic cell viability measurement with microscopic cell counter and microchip. Upon blood draw from 11 healthy volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…A previous study (9) showed that live cells in contact with 0.4% TB for more than 5 min may incorporate the dye, leading to overestimation of the number of dead cells. We therefore evaluated whether the optimum TB concentration for use with flow cytometry had a similar imprecision.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study (9) showed that live cells in contact with 0.4% TB for more than 5 min may incorporate the dye, leading to overestimation of the number of dead cells. We therefore evaluated whether the optimum TB concentration for use with flow cytometry had a similar imprecision.…”
Section: Resultsmentioning
confidence: 99%
“…Intrinsic methods e.g. the GFP microplate assay (Collins LA and Franzblau, 1998) and auto-luminescent mycobacteria expressing the lux operon (Andreu et al, 2010) enable repeated measurements in contrast to endpoint assays like CFU plating and other methods as the Microplate Alamar Blue Assay (Kim et al, 2011). Another advantage of the luciferasebased method is its higher signal to noise ratio as described (Collins, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…The NucleoCounter NC‐3000 enables automated cell counting and analyses of a wide number of samples to be performed at the same time; it is easy to use and also guarantees an excellent precision reducing the data variability due to the operator's work. Other tests used in the clinical routine, such as the determination of cell viability with trypan blue, are characterized by a huge variability of the results 28‐30…”
Section: Discussionmentioning
confidence: 99%